Combining cosmological and local bounds on bimetric theory. Issue 9 (24th September 2021) - Caravano, Angelo; Lüben, Marvin; Weller, Jochen
Abstract: Ghost-free bimetric theory describes two nonlinearly interacting spin-2 fields, one massive and one massless, thus extending general relativity. We confront bimetric theory with observations of Supernovae type 1a, Baryon Acoustic Oscillations and the Cosmic Microwave Background in a statistical analysis, utilising the recently proposed physical parametrisation. This directly constrains the physical parameters of the theory, such as the mass of the spin-2 field and its coupling to matter. We find that all models under consideration are in agreement with the data. Next, we compare these results to bounds from local tests of gravity. Our analysis reveals that all two- and three parameter models are observationally consistent with both cosmological and local tests of gravity. The minimal bimetric model (only β1 ) is ruled out by our combined analysis.